When are do-gooders treated badly? Legitimate power, role expectations and reactions to moral objection inorganizations - WELLMAN, Ned (Institutional Knowledge at Singapore Management University, 2016)
Organization members who engage in “moral objection” by taking a principled stand against ethically questionable activities help to prevent such activities from persisting. Unfortunately, research suggests that they also may be perceived as less warm (i.e., pleasant, nice) than members who comply with ethically questionable procedures. In this article, we draw on role theory to explore how legitimate power influences observers’ responses to moral objection. We argue that individuals expect those high in legitimate power to engage in moral objection, but expect those low in legitimate power to comply with ethically questionable practices. We further propose that these contrasting role expectations influence the extent to which moral objectors are perceived as warm and subjected to social sanctions (i.e., insults, pressure, unfriendly behavior). We test our predictions with 3 experiments. Study 1, which draws on participants’ prior workplace experiences, supports the first section of our mediated moderation model in which the negative association between an actor’s moral objection (vs. compliance) and observers’ warmth perceptions is weaker when the actor is high rather than low in legitimate power and this effect is mediated by observers’ met role expectations. Study 2, an online experiment featuring a biased hiring task, reveals that the warmth perceptions fostered by the Behavior × Legitimate Power interaction influence observers’ social sanctioning intentions. Finally, Study 3, a laboratory experiment which exposes participants to unethical behavior in a virtual team task, replicates Study 2’s findings and extends the results to actual as well as intended social sanctions. (PsycINFO Database Record (c) 2016 APA, all rights reserved)